O rozgraniczaniu statutów i wsysaniu regulacji prawnej (na przykładzie prawa stosowanego do oceny różnych aspektów powołania i funkcjonowania wykonawcy testamentu i zarządcy sukcesyjnego przedsiębiorstwem) - Pazdan, Maksymilian (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The position of the executor of the will is governed by the law applicable to succession (Article 23(2)(f) of the EU Regulation 650/2012), while the position of the succession administrator of the estate of a business of a physical person located in Poland is subject to the Law of 5 July 2018 on the succession administration of the business of a physical person (the legal basis for such solution is in Article 30 of the EU Regulation 650/2012). However, if the court needs to determine the law applicable to certain aspects of appointing or functioning of these institutions, which have a nature of partial or preliminary questions, these laws will apply, as determined in line with the methods elaborated to deal with partial and preliminary questions in private international law. The rules devoted to the executors of wills are usually not self-standing. In such situations, the legislators most often call for supportive application of the rules designed for other matters existing in the same legal system (here — of the legis successionis). This is referred to as the absorption of the legal rules.